STUDY ON THE CHARACTERISTICS OF MICRO-PITTING DAMAGES FOR HIGH POWER DENSITY GEAR TRANSMISSION - LI JiQiang; LIU ZhongMing; WANG DongFei; LI YouHua; ZHANG YanKun (Jixie qiangdu)
the formation mechanism of micro-pitting had been described in this paper,the action relationships of various influencing factors had also been analyzed,and the three main action mechanisms of local contact stress,film thickness ratio of lubricating oil and micro mechanical properties for materials had been regularized.Based on elastohydrodynamic lubrication theory and previous test results for Newtonian fluids,the reasonable calculation method of film thickness for lubricating oils had been determined.Through comparative calculations,the specific effects of oil types,lubricating oil temperatures,transmission torques and gear speeds on the oil film thickness had been analyzed.Combined with the micro-pitting design of gear transmission,feasible ideas and operational methods for lubrication improvements and optimizations had also been given.Finally,through the experimental designs,the correctness of the theoretical analysis had been verified,and the basic data for the anti micro-pitting design of the combination for gears of 18 CrNiMo7-6（material）+ISO-VG220（Lubricating oil） had been goted.